A Simulation Study on the Effect of Cavity Shapes on the Penetration of Linear Shaped Charges with Curved Liners - Dong, S.K.; Cui, A.Y.; Wei, H.K.; Huang, X.D.; Liu, Q.; Pei, G.X. (Проблемы прочности, 2018)
The finite element models of curved-liner shaped charges penetrating aluminum-alloy thin plates were constructed with the ANSYS/LS-DYNA software to analyze the effect of cavity shapes on the charge penetration with curved liners. The cavity height, radius, and spatial dimensions were numerically simulated. Simulation results indicate that these properties are important factors in determining the penetration of curved-liner charges. The penetration depth exhibits an initial increase followed by a decrease with the fixed cavity radius. When the cavity height is fixed, the penetration depth decreases with the cavity radius. When the cavity is semicircular, the penetration depth first increases and then decreases with the cavity radius and height.